2014 IEEE 79th Vehicular Technology Conference (VTC Spring) 2014
DOI: 10.1109/vtcspring.2014.7022769
|View full text |Cite
|
Sign up to set email alerts
|

3D UTD Modeling of a Measured Antenna Disturbed by a Dielectric Circular Cylinder in WBAN Context

Abstract: International audienceThis paper describes a work realized for On-Body antennas characterization: the 3D deterministic modeling of a measured antenna disturbed by a dielectric circular cylinder of finite length. This prediction model is based on the ray-tracing technique for the electromagnetic wave paths search and the Uniform Theory of Diffraction (UTD) for the modeling of the electromagnetic waves interactions with the cylinder. After a detailed description, the model is validated in 3D with measurements ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The studies in [29], [30] have clearly indicated that the direct, reflected and surface diffracted field are not enough to describe the electric field for finite cylinder when the position of the receiving point is higher than the top of the cylinder. Therefore, in this paper, we revise the 3D UTD model to take the edge diffracted field into account .…”
Section: B Modified Model For Finite Cylindermentioning
confidence: 99%
See 2 more Smart Citations
“…The studies in [29], [30] have clearly indicated that the direct, reflected and surface diffracted field are not enough to describe the electric field for finite cylinder when the position of the receiving point is higher than the top of the cylinder. Therefore, in this paper, we revise the 3D UTD model to take the edge diffracted field into account .…”
Section: B Modified Model For Finite Cylindermentioning
confidence: 99%
“…These works on the human body shadowing effects using UTD are mostly carried out in 2D space when transmit antenna (TX) and receive antenna (RX) are at the same height. The investigations in [29], [30] on the 3D UTD cylindrical model show the defect of ignoring the edge diffraction field on the total received field, it means, for a finite 3D cylinder, the top/bottom of cylinder diffracted field have an influence on the total field for single-cylinder scattering problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation